2017
DOI: 10.4028/www.scientific.net/ssp.268.229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing Temperature on Platinum/YSZ Thin Film Fabricated Using RF and DC Magnetron Sputtering

Abstract: This research aims to study the growth and the effect of annealing temperature on the structural properties of Platinum/YSZ/Platinum thin film. The thin films were prepared by RF and DC magnetron sputtering method utilized platinum as electrodes (anode and cathode) and YSZ as electrolyte. Two temperatures of annealing (400 and 600 °C) were conducted onto Platinum/YSZ/Platinum thin film for comparison in this study. Crystalline phase, microstructure and thickness of thin films were evaluated using X-Ray Diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Jaccoud et al [ 10 ] found that the Pt electrode prepared by Pt slurry had better electrochemical performance than that prepared by sputtering. Nurhamizah [ 13 ] found that the Pt electrode with porous structure has better electrochemical performance. Boer [ 14 ] and Xia [ 15 ] found that a certain proportion of YSZ powder in the Pt slurry could improve the porous structure of the Pt electrode and improve the adhesion of the Pt electrode to the YSZ electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Jaccoud et al [ 10 ] found that the Pt electrode prepared by Pt slurry had better electrochemical performance than that prepared by sputtering. Nurhamizah [ 13 ] found that the Pt electrode with porous structure has better electrochemical performance. Boer [ 14 ] and Xia [ 15 ] found that a certain proportion of YSZ powder in the Pt slurry could improve the porous structure of the Pt electrode and improve the adhesion of the Pt electrode to the YSZ electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Yttria-stabilized zirconia (YSZ) is widely employed in technical applications such as thermal barrier coatings [1][2][3], solid oxide fuel cells (SOFC) [4][5][6][7], and oxygen gas sensors [8,9]. Besides its high thermal and mechanical stability, the ionic conductivity of YSZ plays a major role in most of its applications.…”
Section: Introductionmentioning
confidence: 99%